Effect of husbandry system on the technical and economic performance of dairy cattle - De Andrade Ferrazza, Rodrigo [UNESP]; Lopes, Marcos Aurélio; Bruhn, Fábio Raphael Pascoti; De Moraes, Flávio; De Melo Carvalho, Francisval (Universidade Estadual de Londrina, 2017)
This study aimed to investigate the effects of husbandry system on the technical and economic performance of dairy farming. Samples included data from 61 dairy farms from the State of Minas Gerais, Brazil, which were collected between 2002 and 2011. Farms were categorized by type-pasture-based (PB), semi-confinement (SC), and confinement (C)-And technical and economic indexes were compared. In general, the results indicated indexes that are higher than the average for Brazilian farms but lower than those in other countries or technological farms in other Brazilian regions. Milk production was mainly determined by farm size rather than by productivity indexes. Components of the total and effective operational costs that were most significant were feeding followed by labor. The comparative analysis indicated that, although C systems have technical indexes that are superior to those of the PB and SC systems, economic performance was independent of the intensification level. Thus, pasture systems are potentially competitive, provided that the producers are efficient.
Keywords: Dairy farming.; Farm management; Husbandry system; Indexes; Profitability